INT-767 prevents NASH and promotes visceral fat brown adipogenesis and mitochondrial function. Issue 2 (August 2018) - Comeglio, Paolo; Cellai, Ilaria; Mello, Tommaso; Filippi, Sandra; Maneschi, Elena; Corcetto, Francesca; Corno, Chiara; Sarchielli, Erica; Morelli, Annamaria; Rapizzi, Elena; Bani, Daniele; Guasti, Daniele; et al.
Abstract : The bile acid receptors, farnesoid X receptor (FXR) and Takeda G-protein-coupled receptor 5 (TGR5), regulate multiple pathways, including glucose and lipid metabolism. In a rabbit model of high-fat diet (HFD)-induced metabolic syndrome, long-term treatment with the dual FXR/TGR5 agonist INT-767 reduces visceral adipose tissue accumulation, hypercholesterolemia and nonalcoholic steatohepatitis. INT-767 significantly improves the hallmarks of insulin resistance in visceral adipose tissue (VAT) and induces mitochondrial and brown fat-specific markers. VAT preadipocytes isolated from INT-767-treated rabbits, compared to preadipocytes from HFD, show increased mRNA expression of brown adipogenesis markers. In addition, INT-767 induces improved mitochondrial ultrastructure and dynamic, reduced superoxide production and improved insulin signaling and lipid handling in preadipocytes. Both in vivo and in vitro treatments with INT-767 counteract, in preadipocytes, the HFD-induced alterations by upregulating genes related to mitochondrial biogenesis and function. In preadipocytes, INT-767 behaves mainly as a TGR5 agonist, directly activating dose dependently the cAMP/PKA pathway. However, in vitro experiments also suggest that FXR activation by INT-767 contributes to the insulin signaling improvement. INT-767 treatment counteracts HFD-induced liver histological alterations and normalizes the increased pro-inflammatory genes. INT-767 also induces a significant reduction of fatty acid synthesis and fibrosis markers, while increasing lipid handling, insulin signaling and mitochondrial markers. In conclusion, INT-767 significantly counteracts HFD-induced liver and fat alterations, restoring insulin sensitivity and prompting preadipocytes differentiation toward a metabolically healthy phenotype.